Climbing beans in Uganda: A perspective of smallholder farmers on their determinants, associated challenges and implications for research - Takusewanya, Rose; Namayanja, Annet; Adrogu Ugen, Michael; Nkalubo, Stanley; Lapaka Odong, Thomas; Bwogi, Godfrey Vianney (African Journal of Agricultural Research, 2018)
In many parts of the world including Uganda climbing beans are mostly grown in highland areas where population density is high and land is limiting. The objective of this study was to contribute to understanding the current status of the factors affecting productivity of climbing beans among smallholder farmers in Uganda. Kisoro and Kabale districts in the South West were selected for the study. Primary data was collected based on 150 households selected randomly in each district in January and June, 2014. In both districts, climbing beans was ranked as a major crop enterprise for income (72.7%). Most of the interviewed households (84 and 92%) in Kisoro and Kabale respectively appreciated that the major advantage of climbing beans was suitability to areas with limited land. The study revealed practices that seem to integrate the different factors and the various components within each factor promoting ecological or interrelatedness in the production system. Lack of staking materials was ranked by the majority (Kisoro 45% and Kabale 59%) as the most important constraint. Common bean diseases (49%) and pests (45%) were highly ranked in Kisoro as compared to Kabale (13 and 22%). Labour scarcity was ranked by the majority of farmers in Kabale (49%) as compared to Kisoro (19%). Given the importance of climbing beans in the two districts, the study recommends their continued and sustainable intensification.
Keywords: Common bean; Cropping system; Ecological; Food security; Highlands; Legume; Staking